Poetry Narration and Local Identity: A Study of the Construction of “Cultural IP” in Heyuan Hakka Homestays (Verse Version, 2025)
Against the backdrop of digital media and policy-driven rural tourism, this study examines how Hakka homestays in the Heyuan region of Guangdong Province can transition from mere “space provision” to the construction of a poetry-narrative-based cultural IP, thereby fostering tourists’ sense of place identity. Grounded in the intersection of poetic narration, cultural heritage, and semiotic design, the research adopts a case study approach, focusing on: (1) how local symbols and emotions in poetry are transformed into narrative resources; (2) how these resources are narrativized in homestay spaces, experiences, and discourses; and (3) how such narrative-driven IP influences tourists’ place perception, emotional attachment, and sense of belonging. A three-stage model of “narrative resource extraction–narrative translation–identity generation” is proposed, showing that deep narrative integration is more effective than symbolic collage in building sustainable local identity. Theoretically, it extends poetic narration into a narratological framework for tourism and cultural IP construction. Practically, it proposes a “narrative-first” development model for homestays, offering strategic insights for sustainable cultural tourism.
Keywords: Poetry Narration; Local Identity; Cultural IP; Hakka Homestays; Place-making